Pelatihan Penulisan Artikel Sebagai Upaya Percepatan Karir Profesional Guru Sekolah Menengah Pertama di Kota Banjarmasin - Nevy Farista Aristin; Aswin Nur Saputra; Sri Wahyuni; Rixal (Jurnal Pemberdayaan Masyarakat, 2023)
The low understanding and ability to write articles for national journals is one of the main problems for junior high school teachers in Banjarmasin City as a partner school of the Geography Education Study Program, FKIP, Universitas Lambung Mangkurat. This will become an obstacle for teachers in developing their professional careers, so partners need training in writing scientific articles. The aim of this activity is to improve teachers' abilities in writing articles to publish them in credible national journals. The implementation method for this service activity consists of four stages: preparation, implementation, mentoring, and evaluation. This activity was attended by 35 teachers from SMP 35 Banjarmasin and 5 people as representatives from SMP 25 Banjarmasin. The results of this service showed that the teachers gave a positive response of 91%, which means that most teachers understood the material presented by the resource person during the activity. This is also supported by the enthusiasm of the teachers in actively participating in question-and-answer sessions to explore information related to writing credible national and international articles and journals.